2021
DOI: 10.1007/s00345-021-03700-x
|View full text |Cite
|
Sign up to set email alerts
|

Triggers and oncologic outcome of salvage radical prostatectomy, salvage radiotherapy and active surveillance after focal therapy of prostate cancer

Abstract: Purpose Due to the tissue preserving approach of focal therapy (FT), local cancer relapse can occur. Uncertainty exists regarding triggers and outcome of salvage strategies. Methods Patients with biopsy-proven prostate cancer (PCa) after FT for localized PCa from 2011 to 2020 at eight tertiary referral hospitals in Germany that underwent salvage radical prostatectomy (S-RP), salvage radiotherapy (S-RT) or active surveillance (AS) were reported. Prostate sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…reported a range of 3–136 months between HiFU and salvage RT with a median of 39 months. Median time to salvage therapy was also around 30 months in a few other studies, 10–12 while others more consistently showed 12–15 months 13–17 . Importantly, the median PSA values prior to salvage therapies also varied greatly, with a broad range of values reported by certain studies ( e.g .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…reported a range of 3–136 months between HiFU and salvage RT with a median of 39 months. Median time to salvage therapy was also around 30 months in a few other studies, 10–12 while others more consistently showed 12–15 months 13–17 . Importantly, the median PSA values prior to salvage therapies also varied greatly, with a broad range of values reported by certain studies ( e.g .…”
Section: Discussionmentioning
confidence: 91%
“…One of the weaknesses of our studies in particular is the small patient numbers, similar to those of Alongi et al 10 (7 patients); and Rigo et al 9 (24 patients). In contrast, Von Hardenberg et al 17 and Riviere et al 15 reported on much larger number of patients (57 and 100, respectively). We were not surprised by the small number of patients treated in our centres; as HiFU is currently not recommended by practice guidelines, 6 ) it is not covered by the provincial health insurance in Ontario, and offered only by select providers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, one patient presented a locally advanced PCa with evidence of lymph node metastases. Salvage RP is described as oncologically and functionally safe with acceptable side effects [ 25 27 ]. However, that after VTP only in one-third of patients a bilateral nerve sparing could be performed.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies included in this review allowed for up to one further session of cryotherapy as part of the initial focal therapy intervention ( 20 ), with four other studies reporting use of repeated focal ablative intervention for treatment failure ( 21 , 23 - 25 ). Regarding more aggressive whole gland salvage approaches, one recent study quoted progression-free survival after salvage RP and radiation post-focal therapy failure to be 80.4% and 100% at 3 years, respectively ( 40 ). Another study of 82 patients undergoing RP after FT failure demonstrated only a 36% progression-free survival at 3 years but did describe a 12-month continence rate of 83% and minimal perioperative comorbidity ( 41 ).…”
Section: Discussionmentioning
confidence: 99%